Igreja livre no Estado livre: um estudo sobre a Coligação Nacional Pró Estado Leigo e os deputados laicistas na Assembléia Nacional Constituinte de 1933 – 1934 - Oliveira, Edson Douglas de (2024)
The purpose of this thesis is to problematize the discussion on secularism in Brazil. Although the separation of the state has been reaffirmed in all republican constitutions, regardless of the political context, it remains, in its visceral reality, more of a generic intention than an in fact institutional reality. Religious freedom does not eliminate agreements, accommodations or arrangements with which power negotiates spaces in exchange for its political project. In fact, in each cycle, what is shown is that political power increasingly does without these arrangements. In Brazilian History, the Church has only been officially separated from the State, but not formally. The 1891 Constitution was a declaration of intent, but it did not achieve full emancipation from the religious regime, since during the First Republic (1889 - 1930) the Catholic Church began the process of regaining power, culminating in the 1934 Constitution, when it managed to incorporate into the constitutional text the religious amendments proposed by the episcopate and the lay apostolate represented by the Dom Vital Center and the Catholic Electoral League (LEC), that is, the indissolubility of marriage, religious assistance to the armed forces, hospitals and prisons, religious education, recognition of religious marriage with civil effect and the preamble with the name of God in the Constitution. These amendments were opposed by various movements, mainly Protestants, Spiritualists and Masons who, in 1931, organized themselves into a national institution, the National Coalition for the Lay State (CNPEL), which defended the secular state agenda in the May 1933 elections to elect the Constituent Congress of the second republican constitution. Despite its political failure, however, the movement reflected the demands of specific sectors of civil society who realized, at the time, that the route of convergence of Church-State interests, while not threatening to result in an official religion, could, on the other hand, postpone or attenuate the secularization of that same State which, in turn, is increasingly part of a post-modern and progressively secularized world. The debate on the secular state also reveals the existence of secularist thinking that began in the Empire and continues to the present in now days. However, the discussions proposed on the subject since the 19th century, or more specifically from the "Recife School", culminating in Methodio Maranhão, to the more recent days with Isso Chaitz Scherkerkewitz, have not been deepened due to the historical lapses that formed in the middle of this effort to systematize. And since part of these demands were taken up by CNPEL, it can be said that, from the point of view of organized civil society, the discussion is still open today